Literary comprehension competence among senior high school students in Purwokerto - Sudaryanto, Memet; Fadilah, Aldi Nur (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2025)
Literature learning should be designed according to students' characteristics. However, there is still no available competency map that specifically measures students' understanding of literary competencies in schools. This study aims to measure and describe students' competencies in prose, poetry, and drama in Purwokerto. Quantitatively, this study employs a test method based on theoretical construction by developing 30 multiple-choice items that assess students' ability to understand intrinsic and extrinsic elements in prose, poetry, and drama. The study population comprised 5.187 10th-grade students in Purwokerto. A sample of 1.034 students was randomly selected from three public schools in Purwokerto using the PickerWheel application. Instrument validation was conducted using the Aiken Index, yielding a result above 0.75 with five experts. Ekspert merupakan guru dan dosen Bahasa Indonesia yang memenuhi kualifikasi dan kompetensi sebagai ahli di bidang sastra. Reliability was assessed using Cronbach's Alpha and the Test Information Function (TIF) to evaluate the items' ability to explain students' competencies. Through the Rasch Model, this study identified a range of item difficulty levels on a logit scale from -2.55 to 3.17, indicating that the difficulty level of the items falls within a normal range. Based on the analysis of student literature competencies at senior high schools in Purwokerto, the results indicate that the highest student ability score is 100, the lowest score is 0, with a median of 51.11, a standard deviation of 13.89, and the 75th percentile at 59.87.